Ideological grounds of cultural identification of the Crimean tatars: formation contexts - V. G. Napadysta (Ukrainian Cultural Studies, 2017)
The article describes the current ideological grounds of the cultural identity of the Crimean Tatars; the historical and political contexts of their formation is studied, comparative analysis of the activity of the first institutional bodies of the Crimean Tatar national movement – National movement of the Crimean Tatars and Organization of the Crimean Tatar national movement – representations of the ideological longings of the nation, is performed; their role in the creation, expansion, extension of the meaning and practical implementation of the ideological grounds stated in program documents of the named organizations, are determined; it analyzes their differences in the strategic value landmarks and tactical steps, stipulated by them, which have become the reason of different vectors of the mentioned institutional representatives of the Crimean Tatar people in the process of cultural identification, based on unified ideological grounds – national identity, repatriation and national-cultural revival. This study articulates the value of the ideological grounds of the cultural identification of the Crimean Tatars in solving a whole range of problems, caused by the return of the Crimean Tatars to their historical motherland. The traditional orientation of the power establishments of the independent Ukraine on the economic, inter-ethnic, religious segments of the integration process of the Crimean Tatars into the Ukrainian community, neutralized the role of their value orientations and ideological longings, which in its turn did not allow to see the Crimean Tatars as the most proUkrainian power in the Autonomous Republic of Crimea. The importance of the analysis of the ideological grounds of the cultural identity of the Crimean Tatars, differences in strategic values and tactical steps of the various establishments of the Crimean Tatar national movement, is stipulated by the search of models of efficient projects to return and re-integrate the occupied territory of Ukraine, which would include the humanitarian components, based on specific ideological and valuable grounds, but not limited to the economical and political measures.